A new species of Agapophytus Guérin named after the late Donald H. Colless (Diptera: Therevidae: Agapophytinae) - Winterton, Shaun L. (Zootaxa, 2013)
A distinctive new species of Agapophytus Guérin, 1831 (Agapophytus collessi sp. nov.) is described from Australia (Dip-tera: Therevidae: Agapophytinae) and honouring the Dipterist Dr Donald H. Colless.